2015
DOI: 10.1177/1933719114536474
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Hypoxia Induced Beclin 1 Signaling-Mediated Renal Autophagy and Altered Renal Development in Rat Fetuses

Abstract: Hypoxia-affected fetal renal development was associated with renal apoptosis and Beclin 1 signaling-mediated autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 48 publications
1
34
1
1
Order By: Relevance
“…Our previous study demonstrated that high-salt (HS) diets during pregnancy could affect local renin-angiotensin system in the fetal and offspring kidney [7]. In addition, recent work demonstrated that the prenatal insult could affect renal development [8]. However, there has been very limited information about whether the function of renal interlobar arteries can be influenced by prenatal HS intake.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous study demonstrated that high-salt (HS) diets during pregnancy could affect local renin-angiotensin system in the fetal and offspring kidney [7]. In addition, recent work demonstrated that the prenatal insult could affect renal development [8]. However, there has been very limited information about whether the function of renal interlobar arteries can be influenced by prenatal HS intake.…”
Section: Introductionmentioning
confidence: 97%
“…The observed increase in co-localization between LC3 and LAMP2 suggested that autophagic flux was increased and more autophagosomes fused with the lysosomes for degradation 92,93 . Hypoxia during in utero development also led to autophagy induction and apoptosis in the kidney with alteration in Beclin 1, hypoxia inducible factor 1alpha (HIF-1α), AKT, and mTOR signaling 95 . The mechanism by which ischemia up-regulates autophagy is under intense investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the enhanced intestinal autophagy, IUGR pups still had higher mRNA expression of caspase 9 and lower level of Bcl-2 mRNA expression in present study, which indicated that intestinal apoptosis has been up-regulated [42,43] . The over-induced apoptosis might lead to further organ damage [44] . For example, Xia et al [44] proposed that hypoxia induced renal autophagy via Beclin1 signal pathway, enhanced apoptosis and affected the renal development in IUGR rat fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…The over-induced apoptosis might lead to further organ damage [44] . For example, Xia et al [44] proposed that hypoxia induced renal autophagy via Beclin1 signal pathway, enhanced apoptosis and affected the renal development in IUGR rat fetuses. We also observed the similar phenomenon in small intestine of IUGR fetuses (data not published) and newborn IUGR piglets (without feeding colostrum) that over-enhanced autophagy and apoptosis might Effects of IUGR on expression of apoptosis and proliferation related genes in the jejunum.…”
Section: Discussionmentioning
confidence: 99%